Urban Railway System Route Selection in Turkey Based on Socio-Economic and Technical Criteria Using the Analytical Hierarchy Process - Inan, Aslan; Kara, Huzeyfe (SAGE PUBLICATIONS INC, 2022)
With the increased importance of energy all over the world, new energy sources are needed to meet the energy demand. However, the solution to energy demand is not only finding new energy resources but also using currently consumed energy efficiently. Accordingly, decreasing the energy consumption in urban electric railway transport has become an important issue. Investment in urban railway transport is increasing continually because it is more economical, safe, and sustainable than other modes in local transportation. For new investments related to urban railway transport, decision-makers generally make an assessment that will include economic, demographic, and environmental impacts. In this study, a comprehensive top-down decision-making system for urban railway route selection was engineered by taking into account socio-economic criteria as well as technical criteria. In the context of surveys conducted with experts in the choice of railway system routing, five socio-economic criteria (passenger potential, construction cost, integration-access, zoning-ownership, travel time) and five technical criteria (vehicle energy consumption, regenerative energy, traffic operations, power supply system, efficient driving techniques) were determined. In the analysis, the analytical hierarchy process (AHP) method, one of the multi-criteria decision-making methods, was used to determine the best route among alternative routes based on all criteria.
Keywords: public transportation; light rail transit; catenary; Analytical Hierarchy Process; urban railway system route; urban railway energy consumption; Engineering; Transportation